Diseño y construcción de una bomba de pistón alternativa sumergible para el molino multipala americano del A.A.R.N.R. de la UNL. - Pineda Morocho, Wilson Xavier (2015)
In this paper the "Design and construction of alternative submersible pump piston for the American multiblade mill AARNR UNL” was made. A study was performed that allowed characterize the function of the windmill, which allowed obtaining the mechanical potential delivered by the machine. With these parameters it was determined that: The piston diameter, that was built with leather slippers obtaining a diameter of 0.1469m; the thickness of the cylinder liner and flanges that form the compression chamber, which are joined by lug nuts to ensure the sealing. The cylinder liner was designed according to compressive stress, which is generated by the lug nuts and a thickness of 4.75 mm was obtained, the diameter of the lug nuts was calculated based on the theory of design of threaded joints subjected to initial setting with external tensile load and ensure the proposed design. The load pressure produced by the pump, is taken entirely by the bolt body; and the diameter of the shank, that connects the piston rod with the crank system, this designed considering the fatigue failure being obtained a 14.246 mm diameter. All these assuming losses generated from system components and mechanisms. Recovery potential of shallow type well water was determined, this being, 1.305 l / s ensuring a continuous supply of fluid. The whole system allowed drawing water from a well to a depth of 9m, up to a reservoir located 3 meters above the ground, at a rate of 0.5 l / s